1999
DOI: 10.1016/s1097-2765(00)80184-7
|View full text |Cite
|
Sign up to set email alerts
|

SGT1 Encodes an Essential Component of the Yeast Kinetochore Assembly Pathway and a Novel Subunit of the SCF Ubiquitin Ligase Complex

Abstract: We have identified SGT1 as a dosage suppressor of skp1-4, a mutation causing defects in yeast kinetochore function. Sgt1p physically associates with Skp1p in vivo and in vitro. SGT1 is an essential gene, and different sgt1 conditional mutants arrest with either a G1 or G2 DNA content. Genetic and phenotypic analyses of sgt1-3 (G2 allele) mutants support an essential role in kinetochore function. Sgt1p is required for assembling the yeast kinetochore complex, CBF3, via activation of Ctf13p. Sgt1p also associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
394
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(407 citation statements)
references
References 47 publications
12
394
1
Order By: Relevance
“…We are currently conducting yeast twohybrid assays to find possible substrates or protein partners of TaSAP5 and have identified SGT1 and HSC70 as potential interacting proteins. SGT1 was associated with components of the Skp1-Cullin-F-box protein complex in yeast and plants (Kitagawa et al, 1999;Liu et al, 2002), and HSC70 functions as a cochaperone that interacts with unfolded and denatured proteins, which are then subjected to degradation mediated by E3 ligases located in the endoplasmic reticulum (Lee et al, 2009b;Liu and Howell, 2010). Overall, TaSAP5 functioned with cooperative components by catalyzing the transfer of ubiquitin to substrate, but further research will be needed to identify the factors that enhance the protein interaction and polyubiquitin chain assembly in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently conducting yeast twohybrid assays to find possible substrates or protein partners of TaSAP5 and have identified SGT1 and HSC70 as potential interacting proteins. SGT1 was associated with components of the Skp1-Cullin-F-box protein complex in yeast and plants (Kitagawa et al, 1999;Liu et al, 2002), and HSC70 functions as a cochaperone that interacts with unfolded and denatured proteins, which are then subjected to degradation mediated by E3 ligases located in the endoplasmic reticulum (Lee et al, 2009b;Liu and Howell, 2010). Overall, TaSAP5 functioned with cooperative components by catalyzing the transfer of ubiquitin to substrate, but further research will be needed to identify the factors that enhance the protein interaction and polyubiquitin chain assembly in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, the ubiquitin ligase E6-AP was also shown to be associated with Hsc/Hsp70 and to participate in the ubiquitylation and degradation of chaperone clients (Mishra et al, 2009). The interaction of Hsp90 with SGT1, an interactor of the hetero oligomeric SCF ubiquitin ligase complex, points to yet another ubiquitin conjugation machinery that could potentially be involved in CAP (Kitagawa et al, 1999;Mayor et al, 2007;. Finally, the small heat shock protein a-B crystallin that is overexpressed in many neurological diseases was shown to associate with the SCF complex adaptor Fbx4 and to stimulate the Fbx4-mediated ubiquitylation of as yet to be identified substrate proteins (den Engelsman et al, 2003).…”
Section: Figurementioning
confidence: 99%
“…Studies from several groups indicated that SGT1 is required by a diverse range of R genes from different plant species in response to a variety of pathogens [61,[92][93][94][95]. In yeast, SGT1 is a key regulatory protein in centromere function and cell cycle transition and is associated with SKP1 to regulate the activity of the SCF E3 ligase complex [96]. Thus it is speculated that SGT1 functions in plant defense by regulating the activity of the yet unknown SCF E3 ligase that regulates plant defense signal transduction.…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 99%